Pengaruh Pengenaan Sanksi Administratif, Kesadaran Wajib Pajak, dan Penerapan E-Samsat Terhadap Tingkat Kepatuhan Pajak Kendaraan Bermotor Di Provinsi Sumatera Utara - Dirah Santika Sebayang; Reza Hanafi Lubis (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the effect of the imposition of administrative sanctions, taxpayer awareness and application of the E-samsat system on partial and simultaneous motor vehicle tax compliance in Samsat Medan Selatan. This research is a quantitative research using primary data. This study used a sample of 100 taxpayer respondents using accidental sampling technique. The data analysis technique used in this research is Validity Test, Reliability Test, Normality Test, Multiple Linear Regression Test, and Hypothesis Testing (F Test and T Test). The data was processed using SPSS Version 23. The results showed that the Tax Administration Sanctions (X1) and Taxpayer Awareness (X2) were accepted partially, which means that they affect the Motor Vehicle Taxpayer Compliance in North Sumatra Province, while the E-Samsat Program Implementation was rejected. which means it has no effect on Taxpayer Compliance. Meanwhile, Simultaneous Tax Administration Sanctions (X1), Taxpayer Awareness (X2), Implementation of E-Samsat (X3) have a significant effect on Motor Vehicle Taxpayer Compliance in South Medan Samsat.